The Pivotal Role of Islamic Religious Education Teachers in Fostering Moral Development among Senior High School Students: Insights from Indonesian Case Studies - Yogi Rodini; Iskandar Mirza (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in fostering students' morals in the digital era through a comparative case study at SMA Wanayasa (state) and SMK Ma'arif 4 Kebumen (private Islamic). Using a qualitative approach and case study design, data were collected through participant observation, in-depth interviews with 12 informants (teachers, students, and the principal), and analysis of school policy documents. The results of the study revealed three key findings: (1) PAI teachers play a dual role as educators and digital curators who filter negative content while developing platform-based materials such as educational TikTok and the